Health indices for the evaluation and monitoring of health in children and adolescents in prevention and health promotion: a scoping review - Albulena Selmani; Michaela Coenen; Stephan Voss; Caroline Jung-Sievers (BMC, 2021)
Abstract Background Health indicators are used in different settings to monitor health outcomes. Child and adolescent health is arguably one of the most important areas for the application of indices and indicators in prevention and health promotion. Although single health indicators may be better suited to display the complexity of the health status and its determinants, a selected set of indicators will still offer a complex picture. Therefore, it is argued that a group of indicators combined into an index may offer a pragmatic tool that is easier to use in order to inform stakeholders. Methods A scoping review was conducted to identify and describe health indices that monitor and evaluate health of children and adolescents and to appraise the quality and value of the identified indices that may guide the further applications of these indices in particular settings. The three bibliographic databases MEDLINE, EMBASE and PsycINFO were searched and a double screening of titles and abstracts as well as double screening of full texts was performed. Indices contained in these studies were analysed in terms of focus and composition and evaluated in terms of quality criteria. Results The scoping review identified 36 eligible studies with 18 health indices in six thematic categories. Of the identified indices, seven indices focus on anthropometrical variables, three indices focus on special aspects of newborns and five indices focus on oral health. One index assesses "healthy lifestyle" and one "functional ability" whereas one index a combination of different aspects. Most indices are calculated by using primary health data. Conclusions Alone or in combination with single sets of indicators, indices in six major thematic domains may be used as pragmatic tools for monitoring children's and adolescents´ health and the evaluation of interventions in health promotion and prevention settings.